Intention to emigrate after graduation among medical students from two universities in Lima, Peru - Sebastian A. Medina-Ramirez; Alvaro Taype-Rondan (PLoS ONE, 2026)
Objective To determine the prevalence of the intention to emigrate among third- to seventh-year medical students from two private universities in Lima, Peru. Materials and methods Cross-sectional study in third- to seventh-year medical students. To assess associated factors, we calculated adjusted prevalence ratios (aPR) using Poisson regression models. Results Among 508 medical students, 92.1% reported an intention to emigrate. A rising trend was observed within one of the universities evaluated. When analyzing factors associated with the intention not to emigrate, a lower frequency was found among students aged 23–25 compared to those aged 18–22 (aPR: 0.35; 95% CI: 0.13–0.91). Additionally, the intention not to emigrate was more common among those who had completed an external rotation in primary care (aPR: 2.10; 95% CI: 1.18–4.10), and less common among those who preferred a surgical specialty after graduation (aPR: 0.40; 95% CI: 0.20–0.82). Conclusions Our study reveals a high prevalence of the intention to emigrate among third- to seventh-year medical students. It is essential to consider implementing policies that improve training conditions and labor opportunities in order to retain medical talent and strengthen the national health system.